PEMBENTUKAN IDENTITAS MUJAHID GLOBAL PADA TERPIDANA KASUS TERORISME DI INDONESIA (THE FORMATION OF A GLOBAL MUJAHID IDENTITY IN CONVICTS OF TERRORISM IN INDONESIA) - Mirra, Noor Milla; Faturochman, Faturochman (Jurnal Psikologi Indonesia, 2009)
Identity issue is a motivational theme frequently employed in terrorism field, especially since many youth are interested in terrorist organization. Social identity viewed as the appropriate perspective while discussing the dynamics of identity formation due to the better analysis power provided by group psychology than the one explained in individual level. This research aimed to obtain the understanding of psychological dynamic of terrorism behaviors which embrace the identity formation to launch jihad outside the conflict area of convicted the Indonesian Bali Bombing. This research was conducted using phenomenological-based of ethnographic-narrative approach. Five terrorists were chosen as the main informants based on subject variation from preliminary exploration. They consisted of the convicted Indonesian Bali Bombing, three of them had been executed by a firing squad. Narrative analysis was conducted on interview results, documentation (manuscript, personal mail, audio record, audio-visual record and published autobiography) as well as research notes from ground observation. The research was performed in several locations such as the prison where the main informant was jailed and the narrative environment covered the informantsâ hometown, family and school environment. This research found that, first, they subordinized their personal identity into group identity, based on their religious group. Strengthening process of identity took place when any threat existed toward their group. Secondly, the ideologization of jihad occurs in their group in which collective jihad is perceived as an obligation for all moslem. Ingroup mobility differentiates them into those who choose the conventional way and those who choose terror strategy to reach jihad fi sabilillah goal.Keyword: terrorism, identity, group identity, collective Jihad